Influence of seed priming to alleviate the seed dormancy and growth performance in wild moth bean (Vigna aconitifolia (Jacq.) Marechal) - Venkatalakshmi , K; Vijayalakshmi , V; Praimathy , K; Priya , E S S; Subhitsha , R; Parmeswari , K; Sivakumar , P (Plant Science Today, 2025)
To determine the most effective techniques for breaking moth bean seed dormancy and evaluating the impact of seed priming on growth performance and storage potential, experiments were conducted in 2022–23 at the Agricultural College and Research Institute, Eachangkottai, Thanjavur. The study examined various treatments for reducing seed dormancy and enhancing growth performance in wild moth beans. Freshly harvested wild moth bean seeds were subjected to seven different seed priming methods: soaking in water for 4 hours and 6 hours; soaking in gibberellic acid (GA3) at 100 ppm for 30 min. and 60 min; and soaking in potassium nitrate (0.02 M) for 30 min. Compared against untreated control. The results revealed that seeds soaked in GA3 (100 ppm) showed significantly higher germination and superior seedling growth parameters than the other treatments. Regarding the soaking durations, seeds soaked in GA3 (100 ppm) for 60 min recorded higher seed germination and seedling vigour. Seed quality measures were assessed at trimonthly intervals while dormancy broken seeds were kept in Thanjavur's ambient settings for 9 months. As per the results of the storage experiment, wild moth bean seeds were kept for 9 months without significantly reducing their germination rate. Further, a linear reduction was observed in seedling length. A significant increase was recorded in moisture, EC, dehydrogenase, alpha-amylase, and superoxide dismutase. Current research concluded that wild moth bean seeds were treated with GA3 (100 ppm for 60 min) as a seed priming procedure to break dormancy and preserve seed vigour for up to nine months of storage.